THE OPTIMIZATION OF PLANTING PATTERN IN FOOD CROPS USING MULTI OBJECTIVE GOAL PROGRAMMING - Permata Sari, Suci; Filia Sari, Rina; Ulfa Rahayu, Sri (Pena Cendekia Insani, 2025)
In the agricultural sector, food crops are very important in human life because the results of food crops are basic human needs. This study discusses planting patterns to meet the availability of food crops. Planting patterns are very important to implement because it is to increase food production, so that food remains available and does not lack food needs. The study aims to determine the planting pattern in food crops so that the availability of food crops is met. The method used is Multi objective goal programming. Multi objective goal programming has more than one goal function to be achieved by minimizing deviations from the goal. The research obtained with a land area of 72525 Ha, the number of workers is 1000000, the need for organic fertilizer is 639000 kg / Ha, and the need for urea fertilizer as much as 14000000 kg / Ha can optimize planting patterns by planting types of food crop commodities in the of paddy and green beans.